O VIAJANTE DE OS SERTÕES - Gomes, Ginia Maria (Organon, 2003)
This essay analyses the intertextual relationship between Ossertões and the travel chronicle written by the naturalistic travelers thatexplored the Brazilian countryside during the 19th century. Some similaritieshave been identified, such as the “otherness” of the individualtraversing the back-country, the signs along the way, the traveler’s observationson his obstacles, the perception of the melancholic back-countrylandscape, and, mainly, the scientific look, that enables us to approach theEuclides’ narrative to those chronicles. The quotations from several naturalistictravelers proves that Euclides new these narratives. Thus, the presenceof the features which are specific of travel chronicles in Os sertõesevidences the relationship mentioned above and the importance of an analysisin the perspective of travels chronicles.